ANALISIS FAKTOR - FAKTOR YANG MEMENGARUHI AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Afina Survita Prameswari; Rahmawati Hanny Yustrianthe (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This study has investigated the factors that influence the Audit Delay in manufacturing companies from 2010 to 2012. The Independent variable is the size of the Company, Solvency, Profitability, Public Accounting Firm Reputation and Auditor Opinion. While the dependent variable is the Audit Delay. The purpose of this study was to analyze and demonstrate empirically the effect of company size, Solvency, Profitability, Public Accounting Firm Reputation and Auditor Opinion partially or simultaneously. The contribution of this research is to help the Capital Market Supervisory Agency (Bapepam) in determining the policies and regulations concerning the timely submission of financial reports. The population in this research that the manufacturing companies listed in the Indonesia Stock Exchange for the period 2010-2012, a total of 40 manufacturing companies were taken by using purposive sampling. This data uses the secondary data analysis method using multiple regression. The results of this study indicate that the variable does not affect the size of the Company's Audit Delay. The solvency variable has no effect on Audit Delay. Profitability variable effect on Audit Delay. Reputation Public Accounting Firm to Audit Delay effect. Auditor Opinion variable has no effect on Audit Delay. The results of this test also state that these five factors simultaneously influence Audit Delay. Based on the adjusted R2 value of 29.4% indicates that only 29.4% of Audit Delay variable explained by Company Size, Solvency, Profitability, Public Accounting Firm Reputation and Auditor Opinion. While the remaining 70.6% is explained by other variables not examined in this study.